Pengenalan Digital marketing untuk Produk Desa dalam Mendorong Inovasi Bisnis Masyarakat Lokal di Desa Singasari, Jonggol - Vina Ardelia Effendy; Lipur Sugiyanta; Ali Idrus; Fuad Mumtas; Rauhil Fahmi; Deni Utama (Pusat Riset dan Inovasi Nasional, 2025)
The community service program in Singasari Village, Jonggol District, was implemented to address the limitations of digital promotion strategies for local products, despite the community already having relatively good technological literacy. The village has significant potential in the agribusiness sector, supported by fertile land and a population largely engaged in farming and micro, small, and medium enterprises (MSMEs). However, marketing strategies still rely on conventional methods, such as direct sales in traditional markets, which limit market reach. This program was designed to introduce digital marketing as an innovative strategy to enhance the competitiveness of village products while encouraging local business innovation. The implementation method consisted of three stages: pre-activities, core activities, and post-activities. In the pre-activity phase, the team conducted a needs survey with partners, developed strategies and digital marketing materials, coordinated with the community, and prepared participants as well as evaluation instruments in the form of pre-tests and post-tests. During the core activities, participants were introduced to the basic concepts of digital marketing, supporting tools, and hands-on learning through digital platforms. In the post-activity phase, participants’ knowledge was evaluated by comparing pre-test and post-test results to assess improvements in understanding and skills. The evaluation showed significant improvements in participants’ comprehension of digital marketing concepts, ability to promote through social media, consistency in promotion, and skills in creating communicative digital content. Participants also demonstrated greater motivation to market their products online and increased awareness of the importance of branding. The main remaining challenge is the limitation in creating simple visual content, which requires further assistance. Overall, this program had a positive impact by improving promotional skills, expanding market reach, and building a more professional identity for local products. Future recommendations include advanced workshops, regular mentoring, and the establishment of a village content creator community to support the sustainability of the local digital economy.